Results of simultaneous operations for nodular goiter - A. Zh. Kenzhaev; M. Zh. Aliev; E. Zh. Zholdoshbekov (Сибирский научный медицинский журнал, 2021)
In recent years, there has been an increase in patients with thyroid pathology around the world, which is associated with iodine deficiency and often these diseases are combined with other pathologies that require surgical treatment. The aim of our work was to evaluate the effectiveness of simultaneous operations in nodular goiter. Material and methods. The article presents the results of simultaneous operations that were performed in 19 patients with nodular goiter. Echinococcosis of the liver was found in 8 of them, cholelithiasis in 11 (chronic calculous cholecystitis – 7 and recurrent choledocholithiasis – 4). All operations were performed under endotracheal anesthesia from two approaches, and thyroidectomy and resection of the thyroid gland in combination with cholecystectomy (choledochotomy) were performed in 11 and in 8 with echinococcectomy. In addition to conventional examination methods, a fine-needle aspiration biopsy of the thyroid gland was performed in all patients with nodular goiter to exclude proliferative growth and identify the contents of the cyst. Postoperative complications and long-term results were studied (from 3 months to 3.5 years). Results. In the immediate postoperative period, complications arose in 3 cases each (wound suppuration, infiltration and pleurisy). 18 patients were examined up to 3 and 6 months, 15 patients – from one to 2 years, 13 patients – from 2 to 3.5 years; recurrence of goiter and associated diseases (gallstone disease and echinococcosis of the liver) were not found. Conclusion. Simultaneous operations can be performed in cases of nodular goiter combination with echinococcosis and gallstone disease, but under the condition of strict adherence to the rules of the principle of aparasiticity and antiparasiticity in echinococcectomy. When performing simultaneous operations, it is necessary to fully examine the patient, determine the indications and contraindications, the volume of the planned operation, and also pay attention to the preoperative preparation and management of the postoperative period.